Global burden trends and future predictions of ischemic heart disease attributable to air pollution in people aged 60 years and older, 1990–2021 - Zhao, Yuanqin; Liu, Lihui; Fan, Wei; Qi, Man; Liao, Bin (Frontiers in Public Health, 2025)
BackgroundIschemic heart disease (IHD) is one of the leading causes of mortality and disability among the older adults. Studies have shown that air pollution (AP) exacerbates the risk of cardiovascular diseases, particularly IHD, posing significant health threats to older adults and increasing disease burden. Recently, with the rapid advancement of industrial technology, environmental pollution has become increasingly prominent. Therefore, it is of utmost significance to investigate the impact of AP on IHD burden, especially on vulnerable populations such as older individuals.MethodologyGlobal Burden of Disease (GBD) Study 2021 data was used to analyze and quantify contemporary global burden of IHD in individuals aged 60 and above due to AP and for trends for the time period between 1990 and 2021 using disease burden indicators such as deaths, DALYs, YLDs, YLLs and corresponding age-standardized rates (ASRs). Specifically, we are in patterns of disease burden of IHD in various subgroups stratified by age, sex, Sociodemographic Index (SDI), and GBD regions and countries. SDI-based analyses were conducted to explore the association between socioeconomic development and IHD burden attributable to AP. In addition, we employed the Bayesian Age-Period-Cohort (BAPC) model to provide future estimates of IHD burden attributable to AP for persons aged ≥60. This study provides a comprehensive overview of disease burden patterns of AP-related IHD from multiple perspectives.ResultsBetween 1990 and 2021, global IHD burden attributable to AP in individuals aged 60 and above rose in terms of deaths, DALYs, YLDs and YLL, while there was a decline in ASRs. Overall, the disease burden in the older adult population remains high, with older age groups experiencing the greatest burden and the most significant decrease in ASRs. Men consistently faced a higher burden than women. Except for high-SDI regions, the burden increased across all other SDI regions, while ASRs declined across all SDI categories. Regions such as East Asia and South Asia significantly contributed to the global burden, with marked regional differences in ASRs. High-income regions saw a more pronounced decrease in ASRs, whereas low-SDI regions, such as East Asia and South Asia, exhibited slower reductions. China and India together account for over half of the global burden. ASR of IHD attributable to AP generally decreased as SDI increased. Projections for 2036 suggest that the disease burden will continue to rise, while ASRs will gradually decline, with men continuing to bear a higher burden than women.ConclusionAlthough the ASRs of IHD due to AP in individuals aged 60 and older have generally decreased, the absolute number of cases continues to rise. The burden of IHD varies significantly across different genders, age groups, GBD regions, SDI regions, and countries, with older age groups and males exhibiting higher ASRs. In GBD regions such as East Asia and South Asia, as well as in low-SDI regions and developing countries, inadequate healthcare infrastructure and limited AP control exacerbate the impact of AP, resulting in a disproportionately heavy burden. As the global older adult population continues to grow, the health risks associated with AP-induced IHD are expected to worsen, posing an increasing public health challenge. Public health policies should reduce exposure to AP in men and address lifestyle-related factors in this group. In disease-burdened areas, health care systems need to be improved, air quality control policies need to be strengthened, and more efficient health management practices for older individuals need to be adopted. Public health awareness and informing individuals about risks of AP are also necessary for avoiding future disease burdens. Projections for 2036 are for a significant increase in IHD cases and global public health policies should be directed towards reducing AP and developing efficient health care infrastructure to address future challenges.